Oral health status of long‐term care residents in Canada: Results of a national cross‐sectional study. (11th July 2018) - Yoon, Minn N.; Ickert, Carla; Slaughter, Susan E.; Lengyel, Christina; Carrier, Natalie; Keller, Heather
Abstract : Objective: To describe the oral health and oral prosthetic status of long‐term care residents in four Canadian provinces. Background: Oral health can have significant impact on the health and quality of life of older adults. Seniors in long‐term care are highly dependent on care staff for basic activities of daily living and are at risk for poor oral health. Materials and methods: Five hundred and fifty‐nine randomly selected residents were examined from thirty‐two long‐term care homes in Alberta, Manitoba, Ontario and New Brunswick, Canada. Four experienced registered dental hygienists, one in each province, completed a standardised oral health examination with each participant, examining lip health, breath odour, saliva appearance, natural teeth count, gingival inflammation, tooth and jaw pain, denture status, mucosal status and oral health abnormalities. Results: Of the examined residents, 57.6% were dentate, with an average of 16.4 (SD = 8.0) teeth. Most dentate residents had moderate or severe inflammation on at least one tooth (79.6%). Sixty per cent of residents wore dentures, and 43.2% of edentulous residents had poor hygiene of their dentures. Nine per cent of residents required urgent dental treatment for oral health problems such as broken teeth, infection, severe decay and ulcers. Conclusion: This study provides an estimate of the prevalence of oral health problems in residents living in long‐term care homes across Canada and indicates that improvement in oral health care is needed. Future work on development strategies aimed at optimising oral health for long‐term care residents is required.